Giorgio Perissinotto (ed.), Documenting everyday life in early Spanish California. The Santa Barbara Presidio. Memorias y facturas, 1779-1810. Santa Barbara Trust for Historic Preservation, Santa Barbara, CA, 1998; 405 pp. - Arias Álvarez, Beatriz (El Colegio de México, 2017)
Se reseñó el libro: Documenting everyday life in early Spanish California. The Santa Barbara Presidio. Memorias y facturas, 1779-1810.